2016
DOI: 10.1002/adfm.201600437
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Inclusions of Pyridazine‐Based Molecular Rotors in Tris(o‐phenylenedioxy)cyclotriphosphazene (TPP)

Abstract: A new class of rod‐shaped strongly dipolar molecular rotors for insertion into channels of hexagonal tris(o‐phenylenedioxy)cyclotriphosphazene (TPP) has been examined. Seven different 3,6‐disubstituted pyridazines and one singly 3‐substituted system have been prepared and studied by solid‐state nuclear magnetic resonance (NMR), X‐ray powder diffraction, and dielectric spectroscopy. NMR and X‐ray diffraction both show that all but one of these molecular rotors form hexagonal bulk inclusion compounds with TPP. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 61 publications
3
32
0
Order By: Relevance
“…Combined ogranic phases were evaporated to dryness, and the solid residue was recrystallized from minimal amount of boiling HPLC water, giving a yellow solid product (520 mg, 82%). 1 H{ 11 Trimethylammonium 12-Cyano-1-carba-closo-dodecaborate-1-carboxylic acid (9). Cs + salt of 2 (200 mg, 0.66 mmol) was placed in a dry Schlenk flask.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Combined ogranic phases were evaporated to dryness, and the solid residue was recrystallized from minimal amount of boiling HPLC water, giving a yellow solid product (520 mg, 82%). 1 H{ 11 Trimethylammonium 12-Cyano-1-carba-closo-dodecaborate-1-carboxylic acid (9). Cs + salt of 2 (200 mg, 0.66 mmol) was placed in a dry Schlenk flask.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Hexagonal tris( o ‐phenylenedioxy)cyclotriphosphazene (TPP) was employed as a host to investigate the behavior of dipolar rotor assemblies that acted as guests . A variety of different 3,6‐disubstituted pyridazines were synthesized including 3,6‐bis(3‐methylbicyclo[1.1.1]pent‐1‐yl)pyridazine 232 (Figure ).…”
Section: Applications Of Rigid‐linear Linkers In Molecular Rods and Rmentioning
confidence: 99%
“…Hexagonal tris(o-phenylenedioxy)cyclotriphosphazene (TPP) was employed as ah ostt oi nvestigate the behavior of dipolar rotor assembliest hat acted as guests. [286] Av ariety of different 3,6-disubstituted pyridazines were synthesized including 3,6bis(3-methylbicyclo[1.1.1]pent-1-yl)pyridazine 232 (Figure 36). It was seen that the BCP compound formed hexagonal bulk inclusion compounds with TPP and that the in-plane lattice parameters for the hexagonal phases increased with the size of the end group, which in turn controlled the energy barriers for rotation of the pyridazine dipole.O verall it was shown that through ac ombination of molecular design and optimal positioning of the rotor molecules in the host material, ad ramatic lowering of rotational barriers can be achieved.K ey steps in the synthesis of 232 included aG rubbs metastasis reaction to connect the two BCP moieties by ad ouble bond.…”
Section: Molecular Rotorsmentioning
confidence: 99%
“…According to approximate theory (48), the dipole-to-dipole distance of 8.3 Å and a dipole of ∼2.5 Debye (49) promise a Curie temperature T C = ∼120 K in the absence of defects. The use of a larger dipole would raise it further; for pyridazine (4) [μ = ∼4 Debye (50)] the expectation is T C = ∼300 K.…”
Section: Molecularmentioning
confidence: 99%